Answer:
f(-2) = 0
f(0) = -4
f(4) = 12
Step-by-step explanation:
Given the function f(x) = x^2 - 4, we must plug in the values substituting x for each of the answers.
f(-2) = (-2)^2 - 4
-2 times itself is a positive 4, therefore:
f(-2) = 4 - 4
f(-2) = 0
We do the same for each answer.
f(0) = (0)^2 - 4
f(0) = -4
f(4) = (4)^2 - 4
f(4) = 16 - 4
f(4) = 12
Answer:
35%
Step-by-step explanation:
If the graph crosses the x-axis and appears almost linear at the intercept, it is a single zero. If the graph touches the x-axis and bounces off of the axis, it is a zero with even multiplicity. If the graph crosses the x-axis at a zero, it is a zero with odd multiplicity. The sum of the multiplicities is the degree
Answer:
20
Step-by-step explanation: